2009
DOI: 10.1007/s10841-009-9256-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of barriers and orientation on the dispersal ability of wood cricket (Nemobius sylvestris) (Orthoptera: Gryllidae)

Abstract: Dispersal is an important process determining species spread and survival in fragmented landscapes. However, information on the dispersal ability of woodlandassociated invertebrate species is severely lacking. A study was conducted examining the ability of wood cricket (Nemobius sylvestris) (Orthoptera: Gryllidae) to cross small watercourses and to orientate themselves towards habitat edges. A series of experiments were conducted where juvenile (i.e. nymph) and adult wood crickets were released and observed ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…With these observations, the Colorado potato beetle joins other terrestrial insects such as desert locusts and wood crickets, which have been recently shown to readily swim across small watercourses (Heitler et al . 2005; Brouwers and Newton 2010b). The looping behaviour of the swimming Colorado potato beetle is likely to serve, as has been suggested for insects on land, to increase the chances of finding hosts or refuges as they float or swim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these observations, the Colorado potato beetle joins other terrestrial insects such as desert locusts and wood crickets, which have been recently shown to readily swim across small watercourses (Heitler et al . 2005; Brouwers and Newton 2010b). The looping behaviour of the swimming Colorado potato beetle is likely to serve, as has been suggested for insects on land, to increase the chances of finding hosts or refuges as they float or swim.…”
Section: Discussionmentioning
confidence: 99%
“…fasciatus (Gyllenhal) (Coleoptera: Curculionidae) and 1.53 cm/second for Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae); de Sousa et al 2007) or the whirligig beetles (Coleoptera: Gyrinidae) that reach 23.3 cm/second (Xu et al 2012). With these observations, the Colorado potato beetle joins other terrestrial insects such as desert locusts and wood crickets, which have been recently shown to readily swim across small watercourses (Heitler et al 2005;Brouwers and Newton 2010b). The looping behaviour of the swimming Colorado potato beetle is likely to serve, as has been suggested for insects on land, to increase the chances of finding hosts or refuges as they float or swim.…”
Section: Ability To Swimmentioning
confidence: 96%
“…While it seems logical to assume this will have contributed to long-term species losses direct evidence that this is the case, or that rebuilding linkages will benefit species, is scarce (Bailey 2007) although see Quine and Watts (2009), Brouwers and Newton (2010) . Similarly it is hoped that some of the species formerly associated with coppices might flourish in more irregular large-scale mosaics of grassland, scrub and woodland that might develop under large-scale rewilding projects with freeranging large herbivores (Vera 2000).…”
Section: Alternatives Approaches?mentioning
confidence: 99%
“…A larva of L. parvula was observed to disperse 15 m (direct distance) in one night (Kenshin Fujimori, personal communication), which suggests greater dispersal ability than our estimates. The ability to get over gaps or barriers between favorable habitats differs from dispersals within favorable habitats (Brouwers and Newton 2010), but belongs to a ''special '' movement (Van Dyck and Baguette 2005). The dispersal ability in unfavorable environments should be investigated in the future to evaluate the vulnerability of L. parvula to environmental disturbance.…”
Section: Adaptiveness Of Higher Diffusion Coefficients In Rainmentioning
confidence: 99%